1970
DOI: 10.3329/bjch.v33i3.5690
|View full text |Cite
|
Sign up to set email alerts
|

RDWI is Better Discriminant than RDW in Differentiation of Iron Deficiency Anaemia and Beta Thalassaemia Trait

Abstract: Iron deficiency anemia (IDA) and beta-thalassemia trait (BTT) are the common causesof microcytic hypochromic anaemia. Several discrimination indices have beenintroduced to discriminate quickly these similar entities via parameters obtained fromautomated cell counter. The purpose of the study was to compare the value of twodiscrimination indices, red cell distribution width index (RDWI) and red cell distributionwidth (RDW) in differentiation of BTT and IDA. This study consists of 57 cases ofBTT and 72 cases of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
2
9
2
Order By: Relevance
“…4,6,13 Raised RDW in iron deficiency anemia was also noted by Flynn et al, van Zeben et al and Choudhary et al who reported a sensitivity and specificity of 90% and 51%, 94% and 59% and 91.30%and 43.47% respectively. 2,5,18 RDW was found to be 100% sensitive by Santosh et al 10 Limited specificity for iron deficiency anemia was seen in our study as was also observed in studies by Nesa et al, van Zeben et al, Aulakh et al and Flynn et al [4][5][6]18 However, study done by Saroja et al have concluded a higher specificity of 75% and a sensitivity of 47%. 1 Iron deficiency anemia shows raised RDW along with low MCV (microcytic heterogenous anemia) and thalassemia trait forms an important differential diagnosis but shows low MCV and normal RDW (microcytic homogenous anemia).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…4,6,13 Raised RDW in iron deficiency anemia was also noted by Flynn et al, van Zeben et al and Choudhary et al who reported a sensitivity and specificity of 90% and 51%, 94% and 59% and 91.30%and 43.47% respectively. 2,5,18 RDW was found to be 100% sensitive by Santosh et al 10 Limited specificity for iron deficiency anemia was seen in our study as was also observed in studies by Nesa et al, van Zeben et al, Aulakh et al and Flynn et al [4][5][6]18 However, study done by Saroja et al have concluded a higher specificity of 75% and a sensitivity of 47%. 1 Iron deficiency anemia shows raised RDW along with low MCV (microcytic heterogenous anemia) and thalassemia trait forms an important differential diagnosis but shows low MCV and normal RDW (microcytic homogenous anemia).…”
Section: Discussionmentioning
confidence: 61%
“…5 It is the first RBC index to become abnormal during the development of IDA. 4,10 RDW represents the coefficient of variation of RBC volume distribution and is an index of heterogeneity, the In present study, 79% cases had an abnormal RDW and in cases of iron deficiency anemia, 67 out of 79 cases had an abnormal RDW with sensitivity and specificity of 84.81% and 57.14%, respectively. The present study goes in favour of the previous studies done by Pandya et al, Aulakh et al and Nesa et al with sensitivity of 82.27%, 81% and 84.70%, respectively.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Unfortunately, the cost of the test is quite high and the test does not always available in routine practice. (3,15,17) This study involved 202 patients from many regions in Indonesia who underwent thalassemia screening and fulfilled the study's criteria. Most of the subjects were female (74.3%).…”
Section: Discussionmentioning
confidence: 99%
“…(4-11) An appropriate cut-off of reported formulas should be redetermined to increase the sensitivity and specificity of thalassemia screening in one population because the spectrums of mutation of thalassemia are different among population which might result in different values of erythrocytes indices. (12)(13)(14)(15) This study aimed to evaluate red blood cell count (RBC) and some formulas using erythrocytes indices, such as Mentzer index, RDW, RDW index (RDWI), Shine and Lal index (S&L), and Green and King index (G&K) for hemoglobinopathy screening in Indonesia.…”
Section: Indones Biomed J 2017; 9(2): 99-105mentioning
confidence: 99%